2010
DOI: 10.1523/jneurosci.1594-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-Induced Analgesia and Scratching Are Mediated by the Vasopressin-1A Receptor in the Mouse

Abstract: The neuropeptides oxytocin (OXT) and arginine vasopressin (AVP) contribute to the regulation of diverse cognitive and physiological functions including nociception. Indeed, OXT has been reported to be analgesic when administered directly into the brain, the spinal cord, or systemically. Here, we characterized the phenotype of oxytocin receptor (OTR) and vasopressin-1A receptor (V1AR) null mutant mice in a battery of pain assays. Surprisingly, OTR knock-out mice displayed a pain phenotype identical to their wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 78 publications
(97 reference statements)
8
151
1
1
Order By: Relevance
“…Future studies are needed to elucidate the exact neurochemical cascade underlying the observed OXT effect on approach behavior since OXT-induced analgesia in mice, for example, is mediated by vasopressin-1A receptors (Schorscher-Petcu et al, 2010). Similarly, an analysis of which of the various aspects of a pair-bond potentially interact with OXT to promote fidelity in monogamous males may constitute a promising approach to explore the fascinating, albeit tremendously complex, neurobiology of human pair-bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to elucidate the exact neurochemical cascade underlying the observed OXT effect on approach behavior since OXT-induced analgesia in mice, for example, is mediated by vasopressin-1A receptors (Schorscher-Petcu et al, 2010). Similarly, an analysis of which of the various aspects of a pair-bond potentially interact with OXT to promote fidelity in monogamous males may constitute a promising approach to explore the fascinating, albeit tremendously complex, neurobiology of human pair-bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have found that the effects of OT on some social behavior and cognition (e.g., social communication) are mediated by AVP1A receptors (41,42). AVP1A receptors are densely located in the prefrontal, cingulate, pyriform, and entorhinal cortex, as well as the presubiculum and mammillary bodies, but are also found in the amygdala, bed nucleus of the stria terminalis, lateral septum, hypothalamus, and brainstem (43).…”
Section: Ot Reduces Brain Activity Evoked By Negative Emotional Stimulimentioning
confidence: 99%
“…For instance, in male prairie voles (Microtus ochrogaster), septal VP promotes partner preference via OTRs (10), OT induces analgesia in mice via V1aRs (11), and Ile 3 -VP (vasotocin, the nonmammalian form of VP) promotes oviposition in birds via OTRs (12 (13). No fewer than 14 terms are currently used to identify the numerous VP and OT variants, and thus for clarity, we here use "VP" and "OT" to refer to all known homologs of the canonical mammalian forms.…”
mentioning
confidence: 99%